The efficacy of positive parenting training and parenting based on mentalization on improving the mother-child relationship - Narges Ataran; Mohammad Mozafari; Reza Ghorban Jahromi; Sajad Amini Manesh (مجله علوم روانشناختی)
Background: The mother-child relationship is considered one of the important factors in a child’s development. So far, various training methods have been implemented to improve the mother-child relationship, but no study has compared two commonly used approaches in this area that could lead to practical strategies for improving mother-child relationships and promoting children's mental health. Aims: The present study aimed to compare the efficacy of mentalization-based parenting training on improving the mother-child relationship. Methods: The research method was a quasi-experimental design with pre-test and post-test. The statistical population included all mothers and children with behavioral problems who visited Aghaah, Afarinesh, and Nimrokh clinics in Shiraz in 2022. The research sample consisted of 40 mothers and children who were purposefully selected based on inclusion and exclusion criteria and randomly assigned to two experimental groups (positive parenting and mentalization-based parenting). After sample attrition, 15 mothers remained in the positive parenting group and 18 in the mentalization-based parenting group. Participants completed the Parent-Child Relationship Questionnaire (Pianta, 1992) before and after the training. The research findings were analyzed using multivariate covariance analysis in SPSS 23 software. Results: The results of multivariate covariance analysis showed that both positive parenting and mentalization-based parenting training were effective in improving the mother-child relationship (P< 0.001). The results of the Scheffé post hoc test indicated that mentalization-based parenting training had a greater impact on improving the mother-child relationship compared to positive parenting training (P< 0.001). Conclusion: These findings can help parents and psychology professionals choose better methods for nurturing and supporting children and fostering healthier family relationships. Based on the findings, it can be concluded that practitioners may opt for mentalization-based parenting training over positive parenting training for more effective improvement in the mother-child relationship.